EFFECT OF DIFFERENT STORAGE CONDITIONS ON THE QUALITY OF CURRY LEAVES (Murraya koenigii) - Fauziah Tufail Ahmad; Rossalwa Ramli (UPT Penerbitan Universitas Jember, 2017)
Aromatic herb such as Murraya koenigii or curry leaves packed in different thickness ofpackaging materials and stored at different storage conditions were studied. Unsuitablestorage conditions of curry leaves play a major role in reducing its internal and externalquality. Besides that, proper packaging material used also important in reducing postharvestlosses since it acts as a protective barrier from external environmental factors thataccelerates the senescence process. Therefore, it is important to study the suitable storagecondition and packaging material for this herb in preserving its quality and extending theshelf life. Treatments were curry leaves packed in 0.04µm polypropylene (PP) plastic andfurther placed at 5°C, 0.04µm polypropylene (PP) plastic at room temperature, 0.04µm highdensity polyethylene (HDPE) plastic at 5°C, 0.04µm high density polyethylene (HDPE) plasticat room temperature, 0.08µm high density polyethylene (HDPE) plastic at 5°C and 0.08µmhigh density polyethylene (HDPE) plastic at room temperature. The curry leaves were storedfor one month. The parameters evaluated were percentage weight loss, surface color,ascorbic acid and chlorophyll contents, antioxidant activity and sensory evaluation. Theresults indicated that 0.08µm HDPE plastics, followed by 5°C storage temperature was foundto be the best storage condition among all of the treatments by having higher retention ofascorbic acid, chlorophyll content, sensory evaluation score, antioxidant activity and lowerpercentage of weight loss in curry leaves during one month storage period.